2014
DOI: 10.1088/0004-637x/796/2/72
|View full text |Cite
|
Sign up to set email alerts
|

Five-Minute Oscillation Power Within Magnetic Elements in the Solar Atmosphere

Abstract: It has long been known that magnetic plage and sunspots are regions in which the power of acoustic waves is reduced within the photospheric layers. Recent observations now suggest that this suppression of power extends into the low chromosphere and is also present in small magnetic elements far from active regions.In this paper we investigate the observed power supression in plage and magnetic elements, by modelling each as a collection of vertically aligned magnetic fibrils and presuming that the velocity wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The observed increase in the spatial extent of the suppression region with height is in agreement with the results of Moretti et al (2007) and Jain et al (2014). Moretti et al (2007) explained their observations based on a mode-conversion model where the power suppression is primarily due to the partial conversion of p-modes into magnetoacoustic waves that go undetected .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The observed increase in the spatial extent of the suppression region with height is in agreement with the results of Moretti et al (2007) and Jain et al (2014). Moretti et al (2007) explained their observations based on a mode-conversion model where the power suppression is primarily due to the partial conversion of p-modes into magnetoacoustic waves that go undetected .…”
Section: Discussionsupporting
confidence: 90%
“…A quantitative comparison of this dependence between different period bands, and across different channels, indicates that the power suppression is steeper for longer periods and at higher atmospheric heights. Using a theoretical model, Jain et al (2014) showed that the power deficit in the suppression region increases with height above the photosphere. They also found that this behaviour manifests with a larger effect when the magnetic field is stronger, which explains the steeper dependence on magnetic field we found at larger heights.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two such phenomena; e.g. absorption of p-modes in sunspots around 3 mHz (Jain et al, 2014, and references therein) and enhancement of power around 6 mHz, known as acoustic halos, are signatures of wave interaction with the magnetic field (Schunker & Braun, 2011, and references therein).…”
Section: Introductionmentioning
confidence: 99%